PENGARUH PENERAPAN TEKNIK QUICK ON THE DRAW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 IV JURAI TAHUN PELAJARAN 2012/ 2013 - Gustinah, Wira; Rismen, Sefna; Edriati, Sofia (Pendidikan Matematika, 2013)
The Comprehension of math concept are still low atÂ  studentâs in class VIII SMPN 1 IV Jurai. This research aims to determine the studentâs comprehension of math concept that apply Learning Technique Quick On The Draw better than studentâs comprehension of math concept that apply conventional learning in class VIII SMPN 1 IV Jurai. The type of research is experimental by using Randomized Control Group Only Design.Â  The data analysis technique used help of software MINITAB. The result of hypothesis test obtained P-Value = 0,001 is less than Î± = 0,05, then the hypothesis in this research received. In conclusion, studentâs comprehension of math concept that apply Learning Technique Quick On The Draw better than studentâs comprehension of math concept that apply conventional learning in class VIII SMPN 1 IV Jurai.